Role of stem cells in periodontology: A review - Shruti Singh; Deepa Dhruvakumar (Wolters Kluwer Medknow Publications, 2022)
Periodontal regeneration is thought theoretically possible but clinically unpredictable. In periodontitis, inflammation clinically manifests as the deterioration of periodontal tissue support, and the regeneration of weakened tissue is the primary objective of therapy. For years, periodontists have attempted to remedy the damage through a combination of surgical techniques, the use of growth factors with grafting materials, and barrier membranes. Reports also appeared indicating the populations of adult stem cells (SCs) exist in periodontal ligaments of humans as well as animals. This paves the wave in modern cell treatment for periodontal regeneration. This review offers a description of adult human SCs and their potential for periodontal regeneration.